Trends in seed production, growth drivers and present market status of Indian seed industry: An analytical study - MANJUNATHA, B L; RAO, D U M; DASTAGIRI, M B (The Indian Journal of Agricultural Sciences, 2013)
The establishment of National Seeds Corporation (NSC) in 1963 marked the begining of formal seed sector in Indiaand the Indian seed industry has come a long way since then. The seed industry was dominated by the public sector during the first 25 years, ie till 1988. The growth drivers in this period were the ushering of green revolution and special government schemes to increase SRR through programmes like National Seed Project. The liberalisation of seed policy in the form of New Policy on Seed Development (NPSD) 1988 opened the doors for private domestic and multinational seed companies for import of seeds and technologies as well as investment in research and development. The laws and policies thereafter have encouraged private participation, benefitted private seed companies and provided better market access to foreign seed companies. The fact that from 1984 to 1995, around 50-60% of the seed requirement was met by the private sector and in 2010 it was estimated that 80% of turnover in seed business came from private companies establishes the dominance of private seed companies at present. The seed production has quadrupled from 1991 to 2011. The growth was more spectacular in the last decade (2001 to 2011) when seed production tripled with a robust Compound Growth Rate (CAGR) of 15% pa. The growth drivers in this period were the rapid growth of innovations (improved varieties, hybrids and proprietary technologies) and seed markets (especially for Bt cotton, single-cross maize hybrids, hybrid rice, vegetables and few self-pollinated crops), strengthening of IPRs coupled with liberalised seed policies. The future growth drivers of Indian seed industry would be technological breakthroughs to mitigate biotic and abiotic stresses including climate change,favourable regulatory environment for GM crops, government policies to promote investment in seed R&D and infrastructure(both in public and private sector) and providing access to international markets.